Predicting determinants of satisfaction with the life in a sample of elderly students through(a) structural equation model (Revista Brasileira de Ciências do Envelhecimento Humano, 2015)
The goal of this work is to examine the benefits of the Universities of Third Age in Portugal territory on the life of its senior students. It intends to verify if there could be any positive effect on the quality of life of these students, on their vital satisfaction and on their isolation and loneliness. Therefore, it seeks to determine the existence of depressive and anxiety symptoms in subjects. What if the activities offered by the Universities of Third Age promote the decrease of depressive and anxiety symptom. For this study, was collected a sample throughout the Portuguese territory, covering various Universities of the Third Age. The sample was composed only by elderly people who attend the University of the Third Age. The results of this study show that the Universities of the Third Age may allow the combat of social isolation and the decreasement of certain pathological symptoms, such as depression and anxiety. In general, older people who attend these institutions have a very high level of satisfaction with life, do not show feelings of loneliness and show less depressive and anxiety symptoms.